Efficient locationing of dispersion compensating fibers for optical fiber communication systems - Pham Ngoc Luat; Poompat Saengudomlert; Teerapat Sanguankotchakorn; Rajatheva, R.M.A.P; Electricity of Vietnam (EVN) (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This thesis investigates how to efficiently locate dispersion compensating fibers (DCFs) in wavelength division multiplexing (WDM) systems. Using standard single mode fibers (SSMFs) as the transmission medium, we first model a transmission link as a discrete-time filtered channel to quantify the amount of pulse spreading due to chromatic dispersion. Pulse spreading is measured in term of the intersyrnbol interference (ISI) length, where the length of zero corresponds to effectively no pulse spreading. Numerical results indicate that the use of a single DCF on a transmission link is sufficient to cancel out chromatic dispersion for a single-wavelength system at 1,550 nm, a WDM system with the transmission band 1,534.8-1,566 nm and a WDM system with multiple types of fibers connected in series. Based on the above transmission link model, we consider the problem of locating DCFs in WDM ring networks. Assuming that each DCF is designed to completely cancel out the dispersion on its link for the center wavelength of 1,550 nm, we cast the problem of minimizing the number of DCFs as an integer linear programming (ILP) problem subject to the constraints on the maximum allowable end-to-end dispersion for each transmission path. The maximum dispersion value is obtained from the previous ISI length computation. Optimal DCF locations are solved using the optimization tool in MATLAB. In the presence of amplified spontaneous emission (ASE) noise from erbium doped fiber amplifiers (EDFAs) and signal attenuation on transmission links, having fewer DCFs in the system not only reduces the equipment costs but also leads to lower bit error rates (BERs), as demonstrated from the BER analyses based on the obtained optimal DCF locations. Finally, we consider the problem of minimizing the total length (instead of the total number) of DCFs in the system. In this problem, each DCF need not fully cancel out the dispersion on its link as long as the end-to-end dispersion for each transmission path is within the maximum allowable dispersion limits. We cast the problem as a linear programming (LP) problem to be solved by MATLAB. Numerical results demonstrate further improvement on the BERs compared to minimizing the number of DCFs.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Telecommunications, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Optical fiber communication